Educational Level, Work Experience, and Commitment as Determinants of Authentic Leadership Quality Among Elementary School Principals in Surakarta: A Correlational Study - Hidayah, Nur; Purwanto, Purwanto; Giyoto, Giyoto; Rohmadi, Yusup; Wulandari, Fitri (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2024)
Purpose – This study investigates the influence of educational level, work experience, and work commitment on the quality of authentic leadership among elementary school principals in Surakarta. Given the initial findings indicating low levels of authentic leadership among these principals, the study seeks to fill a gap in the literature by exploring how these factors contribute to enhancing leadership quality in an educational context. Design/methods/approach – A correlational research design was employed to explore the relationships between the variables. The study sampled 110 principals from a population of 255 in Surakarta using cluster random sampling. Data were collected through validated and reliable questionnaires measuring work experience, work commitment, and authentic leadership quality, alongside the educational level of the principals. Data analysis included classical assumption tests and regression analysis to determine the significance of the relationships. Findings – The study found significant positive relationships between educational level, work experience, and work commitment with authentic leadership quality. Specifically, regression analysis revealed that higher education levels, greater work experience, and stronger work commitment positively influenced the quality of authentic leadership. These findings suggest that these factors are critical in developing authentic leadership in school settings. Research implications – This research contributes to the understanding of authentic leadership within educational management by identifying key factors that enhance leadership quality among school principals. It provides empirical evidence supporting the importance of formal education, practical experience, and commitment in cultivating effective and authentic leadership.